Evaluation of analogs of mutacin 1140 in systemic and cutaneous methicillin-resistant Staphylococcus aureus infection models in mice - Ju, Min; Joseph, Thushinari; Hansanant, Nopakorn; Geng, Mengxin; Williams, McKinley; Cothrell, Andrew; Buhrow, Andrew Riley; Austin, Frank; Smith, Leif (Frontiers in Microbiology, 2022)
Mutacin 1140 (Mu1140) is a potent antibiotic against Gram-positive bacteria, such as Staphylococcus aureus. The antibiotic is produced by the oral bacterium Streptococcus mutans and is a member of the epidermin family of type AI lantibiotics. The antibiotic exerts its inhibitory activity by binding to the cell wall precursor lipid II, blocking cell wall synthesis, and by disrupting bacterial membranes. In previous studies, the novel K2A and R13A analogs of Mu1140 have been identified to have superior pharmacokinetic properties compared to native Mu1140. In this study, the use of a combined formulation of the Mu1140 K2A and R13A analogs was shown to be more effective at treating MRSA bacteremia than the native Mu1140 and vancomycin. The analogs were also shown to be effective in treating an MRSA skin infection. The use of K2A and R13A analogs may provide a future alternative for treating serious Gram-positive bacterial infections. In a previous study, the Mu1140 analogs were shown to have significantly lower clearances, leading to higher plasma concentrations over time. These properties warranted further testing to determine whether the analogs are effective for the treatment of MRSA bacteremia and acute skin infections. In this study, Mu1140 analogs were shown to be more effective to currently available treatments for systemic and skin MRSA infections. Further, the study clearly shows that the new analogs are superior to native Mu1140. These findings support continued drug product development efforts using the K2A and R13A Mu1140 analogs and these analogs may ameliorate the outcome of serious bacterial infections.